Relationship between migraine and sleep disorders in adolescents - Lina Waty; Supriatmo Supriatmo; Bistok Saing (Indonesian Pediatric Society Publishing House, 2013)
Background Headaches and sleep disorders may influence academic performances, personality, memory, and interpersonal relationships. Migraine is the most common headache type seen in adolescents. Although headaches and sleep disorders are believed to be related, there has been little study in this area. Objectives To assess the relationship between migraine and sleep disorders in adolescents and compare different types of sleep disorders found in adolescents with migraine vs. healthy adolescents. Methods We conducted a cross sectional study in December 2009 on students of three junior high schools in the Secanggang District, Langkat Regency, North Sumatera. We included adolescents aged 12 to 17 years who suffered from migraines, as defined by the International Cftissificaticm of Headache Disorders, 2nd edition criteria (ICHD-II), and h ealthy adolescents who did not experien ce migraines as the control group. Parents filled questionnaires on their child's sleep patterns for one week. Results A total of 100 adolescents were enrolled in the study, consisted of 50 adolescents in the migraine group and the others 50 in the control group. There was a significant difference in the incidence of sleep disorders between the two groups (76% and 30%, in the case and control groups, respectively; P= 0.0001). Moreover, significant differences were also found in the prevalence of different sleeping disorder types between the case and control groups, i.e. insomnia (62% and 30%, respectively; P= 0.003), sleep apnea (56% and 16%, respectively; P= 0.0001), restlessness (56% and 18%, respectively; P= 0.0001) , parasomnia (76% and 10%, respectively; P= 0.0001), narcolepsy (42% and 16%, respectively; P= 0.008), and excessive daytime sleepiness (50% and 26%, respectively; P= 0.023). Conclusions Migraine in adolescents is significantly associated with sleep disorders. Parasomnia is the most common type of sleeping disorder observed in adolescents with migraines in our study.